Effect Of Different Feeding Systems On Growth Performance And Carcass Traits Of Growing And Finishing Pigs - Ramesh, V.; Edwin, S.C.; Murugan, M.; kumar , S. Vasantha (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was carried out with twenty four Large White Yorkshire weaned piglets to find out the effect of different feeding regimes on growth performance of pigs. The piglets at weaning were randomly divided into four groups of six each. The first group (T1 ) fed with 100 per cent concentrate and the same was replaced on DM basis with hostel food waste at 50 per cent level (T2) , the third group (T3 ) 50 % concentrate with 25 % swill and 25 % Hedge Lucerne and the fourth group (T4) was fed with 50 % swill, 25 % concentrate and 25 % Hedge Lucerne . A significantly (P<0.01) higher weight gain and average daily gain from weaning to seven months of age were found in T2 ( 59.01 ± 1.32 kg and 393.00 ± 58.28 gm). Similarly the feed conversion efficiency was also better in T1 (3.60 ± 0.15 ) than the other groups. The slaughter and carcass weight were significantly (P<0.01) higher in T2 group ( 72.83 ± 4.08 and 52.50 ± 7.75 kg) than the other groups. The T2 group recorded significantly (P<0.01) higher back fat thickness and loin eye area.